Ureteric Injury due to the Use of LigaSure - Muazzam Tahir; William Gilkison (Case Reports in Urology)
Background. LigaSure is a bipolar clamping device used in open and laparoscopic surgeries for producing haemostasis in vascular pedicles up to 7 mm in diameter (“Covidien LigaSure technology: consistent, reliable, trusted vessel sealing,” 2012). The use of LigaSure has made securing haemostasis and tissue dissection relatively easy especially in laparoscopic surgery; however, if not used with care it can cause damage to the surrounding structures through lateral spread of energy. Case Report. This case report discusses the induction of a thermal ureteral injury associated with the use of LigaSure. An 80-year-old gentleman was operated for bowel cancer. LigaSure was used for securing haemostasis and tissue dissection. Postoperatively, he was found to have damage to the right ureter secondary to lateral spread of energy from the jaws of LigaSure with high abdominal drain output. Conclusion. Judicious and careful use of electrosurgical devices should be done to prevent inadvertent damage to the surrounding structures. Early recognition and involvement of a urologist can prevent long-term complications.